(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Assessing entrepreneurial ability is fundamental for understanding and predicting success in business ventures. This paper explores methodological approaches to assessing entrepreneurial ability, with a particular focus on utilizing surveys as a tool for self-assessment. A survey consisting of 20 questions was administered to a sample of aspiring entrepreneurs, aiming to capture various dimensions of entrepreneurial skills, traits, and behaviors. Based on the survey results, a comprehensive assessment of individuals’ perceived abilities in business endeavors was calculated. The paper discusses the design and implementation of the survey instrument, including the selection of questions and the rationale behind their inclusion. It also examines the process of data collection and analysis, highlighting key findings and insights derived from the survey responses. Furthermore, the paper discusses the strengths and limitations of using self-assessment surveys in evaluating entrepreneurial ability, including considerations related to validity, reliability, and potential biases. By leveraging survey data, this study contributes to the ongoing discourse on methodological approaches to entrepreneurial assessment, providing valuable insights into the self-perceived competencies of aspiring entrepreneurs. The findings offer implications for entrepreneurship education, training, and talent development initiatives aimed at fostering the growth and success of future business leaders.